Three essays on banking excess liquidity in Economic Community of Central African States (ECCAS) - (:unkn) unknown (My University, 2012)
This thesis is based on three essays focused on analysis of the excess liquidity in the CEMAC countries. The first one identifies the determinants of excess liquidity in developing countries by studying the case of CEMAC member countries from 1985 to 2002. The GMM estimator used has shown that the excess liquidity in Central Africa derived from both the prudence of commercial banks and exogenous factors. The precaution of Commercial Banks can be explained by the financial crisis in 1980s, the restructuring of the banking system, the instability of deposits and a very risky economic environment. The increasing in oil prices fueling excess reserves due to the low absorption capacity of countries in the region. In the second essay, it was discussed the transmission channels in Central Africa. The VAR model used has shown that the interest rate channel is the lowest. This is exactly the lack of a financial market that does not allow ensuring the function of the recycling of liquidity and the transmission of monetary policy. At the last essay, it was developed a forecasting model of inflation in Chad which is member of CEMAC countries. BVAR models have been shown in Chad to be more effective than traditional tools (AR, ARIMA and VAR). A sensitivity analysis undertaken by the Bayesian approach indicates that the excess liquidity would exert inflationary pressures.
Keywords: African Research